2002
DOI: 10.1161/hs0202.102882
|View full text |Cite
|
Sign up to set email alerts
|

Physician Advice, Patient Actions, and Health-Related Quality of Life in Secondary Prevention of Stroke Through Diet and Exercise

Abstract: Background and Purpose-Healthy diet and exercise are recommended for secondary prevention in stroke patients. We examined the prevalence of persons with stroke who received physician advice for, and engaged in, dietary change and exercise, and we also sought to determine whether engaging in these actions was associated with differences in health-related quality of life (HRQOL). Methods-Data are from 51 193 participants in the 1999 Behavioral Risk Factor Surveillance System, a state-based telephone survey. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 34 publications
1
73
0
4
Order By: Relevance
“…25,26,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Interpersonal skills such as active listening, relationship building, and communication skills are fundamental and necessary (but perhaps not sufficient) to the provision of high-quality and equitable health care. Finally, this analysis also underscores the fact that stereotyping and bias is not simply a product of the individual provider but is caused by features of the health care setting that decrease cognitive capacity, such as fatigue, overload, and time pressure.…”
Section: Future Directions: Research and Interventionmentioning
confidence: 99%
“…25,26,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Interpersonal skills such as active listening, relationship building, and communication skills are fundamental and necessary (but perhaps not sufficient) to the provision of high-quality and equitable health care. Finally, this analysis also underscores the fact that stereotyping and bias is not simply a product of the individual provider but is caused by features of the health care setting that decrease cognitive capacity, such as fatigue, overload, and time pressure.…”
Section: Future Directions: Research and Interventionmentioning
confidence: 99%
“…92 Indeed, a recent study found that physician recommendations to exercise resulted in a doubling of the likelihood that stroke survivors would exercise. 93 This cost-effective intervention, which is now strongly supported by sound research, holds tremendous promise. The challenge for healthcare providers is to bring this promise to fruition.…”
Section: Future Directionsmentioning
confidence: 99%
“…Exercise reduces blood pressure, decreases body weight, and improves other risk factors, including metabolic syndrome [89]. The role of the health provider is important and the physician's advice regarding physical activity to patients can significantly modify exercise and diet style, including those with a prior stroke [90]. One recent observation of note is associated with the onset of stroke with physical activity [91].…”
Section: Physical Inactivitymentioning
confidence: 99%